The use of portfolio credit risk models in Central Banks - Ulrich Bindseil; Han van der Hoorn; Ken Nyholm; Henrik Schwartzlose; Pierre Ledoyen; Wolfgang Föttinger; Fernando Monar; Bérénice Boux; Gigliola Chiappa; Noëlle Honings; Ricardo Amado; Kai Sotamaa; et al. (European Central Bank (ECB), 2007)
This report summarises the findings of the task force. It is organised as follows. Section 2 starts with a discussion of the relevance of credit risk for central banks. It is followed by a short introduction to credit risk models, parameters and systems in Section 3, focusing on models used by members of the task force. Section 4 presents the results of the simulation exercise undertaken by the task force. The lessons from these simulations as well as other conclusions are discussed in Section 5.
Keywords: 330; Kreditrisiko; Portfolio-Management; Zentralbank; EU-Staaten